The Effect of Plyometric Training Single Leg Box Hop from Lunge and Low to Medium Hurdle Jump on Leg Muscle Explosive Power in Sabre Fencing Athletes - Sakti, Marvin Tri; Purnamasari, Ira; Novian, Geraldi (Indonesian Journal of Sport Management, 2025)
This study aims to determine the effect of plyometric training Single Leg Box Hop from Lunge and Low to Medium Hurdle Jump on leg muscle explosive power in sable fencers. Leg muscle explosive power is one of the important components in the performance of fencing athletes, especially sable fencing which requires speed, explosion, and effectiveness in attacks such as lunges and fleches. Method This study was conducted using an experimental method using a two-group pre-test-posttest design. The subjects were 8 sable fencing UKM athletes from the Indonesian University of Education (UPI). Using total sampling. The instrument used was Standing Broad Jump to measure leg muscle explosive power. The training program was carried out for 4 weeks with a frequency of 2 times a week. Data analysis used a paired sample t-test to see the increase in explosive power before and after treatment. The results showed that both Single Leg Box Hop From Lunge and Low To Medium Hurdle Jump training had a significant effect on increasing leg muscle explosive data.